The microbiota-gut-brain axis in irritable bowel syndrome: expert guidance on diagnosis and management - Palaniswamy, K. R. (International Journal of Research in Medical Sciences, 2025)
Irritable bowel syndrome (IBS) is a prevalent functional gastrointestinal disorder marked by chronic abdominal pain, discomfort, and altered bowel habits, significantly affecting quality of life and healthcare costs. This review explores the role of the microbiota-gut-brain axis in IBS pathogenesis and discusses current and emerging management strategies. Dysbiosis, characterized by gut microbiota imbalance, contributes to inflammation, increased intestinal permeability, and disrupted gut-brain communication, exacerbating symptoms. Stress further impacts the gut microbiome, underscoring the psychological and gastrointestinal link in IBS. Diagnosis remains complex due to overlapping symptoms with other functional gastrointestinal disorders. The Rome IV criteria are standard for diagnosis, but Rome III may be more sensitive in India. Treatment is personalized, integrating dietary and lifestyle modifications with pharmacological options. Antispasmodics (e.g., mebeverine) provide pain relief, while rifaximin targets gut bacteria, and antidepressants address psychological factors and visceral hypersensitivity. Probiotics, especially Bifidobacterium and Lactobacillus strains, show promise in modulating gut microbiota and enhancing gut-brain signaling. Future IBS management aims to develop non-invasive biomarkers for improved diagnosis and identify novel therapeutic targets. Enhancing treatment accessibility and affordability, particularly in developing regions, remains critical. This review highlights the importance of understanding the microbiota-gut-brain axis to advance effective, individualized IBS treatments.